Neurotoxicidad retardada por pesticidas en bovinos (1983)
A natural case of delayed neurotoxicity by pesticides in bovines of lbague Tolima (Colombia) is reported. 17 adults zebu cattle showed posterior limbs ataxia, progressive paralisis, lateral decubitus muscular atrophy and opisthotonos. From those animals only eight were submitted to rigorous clinical exam, assays of some treatments and determination of colinesterase. The eight animals were slaughtered and toxicologic and histopathologic analysis were carried out. Inhibition of blood colinesterase and high concentrations of carbamates and organochlorides in viscera nervous and muscular tissues were demonstrated as well as nervous and muscular lesiones were seen.